Modified Activation Process for Supercapacitor Electrode Materials from African Maize Cob - Kigozi, Moses; Kali, Ravi; Bello, Abdulhakeem; Padya, Balaji; Kalu-Uka, Godwin Mong; Wasswa, John; Kumar Jain, Pawan; Azikiwe Onwualu, Peter; Dzade, Nelson Yaw (Materials, 2020)
In this work, African maize cobs (AMC) were used as a rich biomass precursor to synthesize carbon material through a chemical activation process for application in electrochemical energy storage devices. The carbonization and activation were carried out with concentrated Sulphuric acid at three di erent temperatures of 600, 700 and 800 C, respectively. The activated carbon exhibited excellent microporous and mesoporous structure with a specific surface area that ranges between 30 and 254m2 g􀀀1 as measured by BET analysis. The morphology and structure of the produced materials are analyzed through Field Emission Scanning Electron Microscopy (FESEM), Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Di raction (XRD), Boehm titration, X-ray Photoelectron Spectroscopy (XPS) and Raman Spectroscopy. X-ray photoelectron spectroscopy indicates that a considerable amount of oxygen is present in the materials. The functional groups in the activated carbon enhanced the electrochemical performance and improved the material’s double-layer capacitance. The carbonized composite activated at 700 C exhibited excellent capacitance of 456 F g􀀀1 at a specific current of 0.25 A g􀀀1 in 6MKOH electrolyte and showed excellent stability after 10,000 cycles. Besides being a low cost, the produced materials o er good stability and electrochemical properties, making them suitable for supercapacitor applications.
Keywords: Biomass; Acid-activation; Oxidation; Specific capacitance; Electrode material